The deletion of M4 muscarinic receptors increases motor activity in females in the dark phase - Valuskova, Paulina; Forczek, Sandor T; Farar, Vladimir; Myslivecek, Jaromir (Brain and behavior, 2018)
OBJECTIVES: M4 muscarinic receptors (MR) presumably play a role in motor coordination. Previous studies have shown different results depending on genetic background and number of backcrosses. However, no attention has been given to biorhythms. MATERIAL AND METHODS: We therefore analyzed biorhythms under a light/dark cycle obtained telemetrically in intact animals (activity, body temperature) in M4 KO mice growth on the C57Bl6 background using ChronosFit software. Studying pure effects of gene knockout in daily rhythms is especially important knowledge for pharmacological/behavioral studies in which drugs are usually tested in the morning. RESULTS: We show that M4 KO mice motor activity does not differ substantially from wild-type mice during light period while in the dark phase (mice active part of the day), the M4 KO mice reveal biorhythm changes in many parameters. Moreover, these differences are sex-dependent and are evident in females only. Mesor, night-day difference, and night value were doubled or tripled when comparing female KO versus male KO. Our in vitro autoradiography demonstrates that M4 MR proportion represents 24% in the motor cortex (MOCx), 30% in the somatosensory cortex, 50% in the striatum, 69% in the thalamus, and 48% in the intergeniculate leaflet (IGL). The M4 MR densities were negligible in the subparaventricular zone, the posterior hypothalamic area, and in the suprachiasmatic nuclei. CONCLUSIONS: We conclude that cholinergic signaling at M4 MR in brain structures such as striatum, MOCx, and probably with the important participation of IGL significantly control motor activity biorhythm. Animal activity differs in the light and dark phases, which should be taken into consideration when interpreting the results.
Keywords: Male; Behavior, Animal; motor cortex; Receptor, Muscarinic M4; receptor muskarinový M4; Motor Activity; intergeniculate leaflet; Mice, Inbred C57BL; sex differences; Animals; striatum; Sex Factors; temperature; biorhythm; Mice; chování zvířat; Models, Animal; myši inbrední C57BL; thalamus; mužské pohlaví; Female; pohybová aktivita; periodicita; Periodicity; ženské pohlaví; modely u zvířat; suprachiasmatic nuclei; mozek; zvířata; motor activity; myši knockoutované; sexuální faktory; Brain; M4 muscarinic receptor; Mice, Knockout; myši